The Evaluation and Hazard Classification of Toxicological Information for Workplace Hazardous Materials Information System Material Safety Data Sheets - Côté, Rosanne; Davis, Hugh; Dimock, Colleen; Korpan, Mary; Loewen, Ken; Segal, Lawrence M. (Regulatory toxicology and pharmacology, 1998)
Hazardous materials used occupationally in Canada are subject to the legislated requirements of the Workplace Hazardous Materials Information System (WHMIS). This paper describes the administrative framework of WHMIS and how toxicological data are evaluated to determine if a substance triggers WHMIS classification for the toxicological endpoints of acute toxicity, skin irritation, eye irritation, corrosion, dermal sensitization, respiratory sensitization, chronic toxicity, mutagenicity, teratogenicity/embryotoxicity, and carcinogenicity. Problems encountered with the information on material safety data sheets are also discussed for each of the toxicological endpoints.